1987
DOI: 10.1051/apido:19870401
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering Performance of Honey Bee Colonies Heavily Infested With Acarapis Woodi (Rennie)

Abstract: SUMMARYThree groups of honey bee colonies (N = 30) were overwintered on a mountainside (2800 M) in northeastern Mexico. Infestation levels of Acarapis woodi in the three groups averaged 0, 28.2 and 86.0 % for the control, moderately, and heavily infested colonies, respectively. Heavily infested colonies were 28 % smaller than controls (P < 0.01) in the fall. Adjusting for this, heavily infested colonies lost significantly more bees than either the moderately infested group, or the controls (P < 0.0001). Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 21 publications
0
56
0
2
Order By: Relevance
“…personal observation). Other studies have shown that winter mortality rates in colonies with tracheal mites are generally higher in cold climates (Eischen, 1987;Otis and Scott-Dupree, 1992). Honeybees in a colony with a moderate infestation will have reduced capability to use their flight muscles to generate thoracic heat due to mites and associated debris blocking the prothoracic tracheae (Komeili and Ambrose, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…personal observation). Other studies have shown that winter mortality rates in colonies with tracheal mites are generally higher in cold climates (Eischen, 1987;Otis and Scott-Dupree, 1992). Honeybees in a colony with a moderate infestation will have reduced capability to use their flight muscles to generate thoracic heat due to mites and associated debris blocking the prothoracic tracheae (Komeili and Ambrose, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a lightly infested beehive shows low honey production and low pollination capacity (Eischen, 1987;Eischen et al, 1989;Otis and Scott-Dupree, 1992). A heavy load of A. woodi results in colony loss during winter (Eischen, 1987;Eischen et al, 1989;McMullan and Brown, 2009). Such damage is derived from injuries to individual bees, including nutritional loss, damage to tracheal Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Tracheal mite infestation in Japanese honey bees colonies infested with tracheal mites collapse during winter and early spring (Dawicke et al, 1992;Eischen, 1987). A. cerana japonica colonies collapsed in summer, as well as in winter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A. woodi sucks the haemolymph from honeybees (Pettis and Wilson 1996) and causes damage to both individuals (Bailey and Lee 1959;Eischen 1987;Liu 1990;Komeili and Ambrose 1991) and colonies (Eischen et al 1989;Bailey and Ball 1991;Otis and Scottdupree 1992). The most critical damage inflicted by tracheal mites on the honeybee colonies is colony death during winter (Clark 1991;McMullan and Brown 2009;Maeda 2016).…”
Section: Introductionmentioning
confidence: 99%